Management of ecosystem services in mountain forests: Review of indicators and value functions for model based multi-criteria decision analysis. (August 2017) - Blattert, Clemens; Lemm, Renato; Thees, Oliver; Lexer, Manfred J.; Hanewinkel, Marc
Graphical abstract: Highlights: Practical indicators to assess the effect of forest management on ES are selected. The focus is on indicators directly derivable from forest model outputs. The scales are that of the single forest stand and of the forest management unit. Standardisation approaches (value functions) are presented for each indicator. The results can be used to build a holistic multi-criteria decision framework. Abstract: The main ecosystem services (ES) central European mountain forests provide are: protection against gravitational hazards, timber production, recreation, biodiversity conservation and carbon storage, which are all in high demand. These demands make managing mountain forests a challenging task, involving manifold synergies and conflicts between the different ES. There is therefore an urgent need for appropriate concepts and tools for support decisions in forest management and planning (FMP) to take into consideration all ES and to manage the wide variety of information types, parameters and uncertainties involved in assessing the sustainability of ES. Multi-criteria decision analysis (MCDA) provides a suitable set of methods for sustainability evaluations. In this study sustainability means the persistent fulfilment of the required ES. To address all the phases of the FMP process, MCDA and forest models should be applied together, with indicators providing the main interfaces to combine them. This paper aims to: i) review assessment approaches in order to select appropriate and widely accepted indicators for measuring and assessing the effects of different silvicultural management alternatives on forest ES, and ii) present additional standardisation approaches (value functions) for each indicator. Standardisations are necessary to make the different ES comparable and to study synergies and trade-offs between different management objectives in MCDA. The main ES in central European mountain regions are considered, with a clear focus on those indicators that are directly derivable from forest model outputs and that can refer to sustainable forest management practices. The scales considered are that of the single forest stand and of the larger forest management unit. A holistic indicator-based analysis framework for FMP in mountain forests can be built using the indicators and value functions described. The influence of different management alternatives on ES can then be evaluated, taking into consideration the instruments and information on forest management (forest models, inventory) available. All indicators are selected according to existing and approved approaches that only require data that is normally available in operational forest management. The framework can thus be an important element in developing a decision support system for FMP in mountain forests.